Instrument-assisted soft tissue mobilization in healthy adults acutely changes the tissue stiffness - Ema, Ryoichi; Iino, Yuta; Nomura, Yuta; Furusawa, Tomoki; Hirata, Kosuke; Yoshitake, Yasuhide; Akagi, Ryota (International Journal of Sports Medicine, 2024)
This study clarified whether instrument-assisted soft tissue mobilization (IASTM) on the plantar surface changes abductor hallucis and plantar fascia stiffness at rest and medial longitudinal arch height under low- and high-loading conditions. IASTM was performed to one foot of the twenty-eight young men (IASTM condition), and the other foot of them was assigned to the control condition. Using ultrasonography, the resting shear wave propagation velocity of the abductor hallucis and plantar fascia and navicular height in a seated posture were determined. The foot contact area during quiet standing was measured using a foot-scan system. The shear wave propagation velocity of the plantar fascia significantly decreased by 10.8% in the IASTM condition but did not change significantly in the control condition. The magnitude of change in the shear wave propagation velocity of the plantar fascia was negatively correlated (r=− 0.660) with the shear wave propagation velocity of the plantar fascia before IASTM. The interaction of time and condition was not significant for the shear wave propagation velocity of the abductor hallucis, navicular height, or foot contact area. The current study revealed that IASTM on the plantar surface affected tissue stiffness but did not change the structure of the foot.
Keywords: Abductor hallucis; Foot contact area; Navicular height; Plantar fascia; Shear wave propagation velocity